Nurses at the Frontline: A Comprehensive Review of Nursing Contributions to Infection Prevention and Patient Safety - Alharbi, Tagreed Saud; Alahmari, Khairiah Ali; Al-Osaimi, Jaza Ghazi Awad Allah; Alhafie, Taghreed Rabie; Al-Harbi, Samar Ali Raziq; Almalki, Abdullah Suwaylih Sultan; Althobaiti, Bander Safar M; Al-Thaqafi, Abdulhadi Abdullah M; Al-Thaqafi, Mohammed Abdullah M; Alahmari, Khalid Ali Mohammed (Journal of Posthumanism, 2024)
Healthcare-associated infections (HAIs) remain one of the most significant threats to patient safety, contributing to prolonged morbidity, extended hospital stays, increased healthcare costs, and preventable mortality worldwide. As frontline healthcare providers, nurses play a pivotal role in infection prevention through continuous surveillance, adherence to evidence-based practices, patient education, and implementation of infection control protocols. This review aims to comprehensively examine the multifaceted contributions of nurses to infection prevention and patient safety across diverse healthcare settings. Utilizing a systematic analysis of recent literature from 2018 to 2024, the study explores nursing interventions in hand hygiene, aseptic technique, antimicrobial stewardship, device-associated infection control, and outbreak management. The review also evaluates the direct impact of nursing roles on reducing infection rates, improving patient outcomes, and enhancing the overall safety culture within hospitals. Additionally, it addresses organizational, technological, and behavioral challenges affecting nursing effectiveness and discusses strategic frameworks for empowering nurses as leaders in infection control. Findings highlight that effective nursing-led infection prevention strategies significantly reduce HAIs and promote safer healthcare environments. The review concludes with recommendations for strengthening nursing capacity through education, policy support, and integration of innovative technologies to sustain long-term infection control success.